(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Childhood overweight and obesity have become major public health challenges worldwide. According to the World Health Organization, the prevalence of excess body weight among children and adolescents has increased dramatically over the past decades, affecting both developed and developing countries. Excess body weight in childhood is not merely a cosmetic issue but a serious medical condition associated with a wide range of comorbidities that can affect almost every organ system. These comorbid conditions may begin in childhood and persist into adulthood, significantly increasing morbidity, mortality, and healthcare costs. Comorbidity refers to the presence of one or more additional diseases or disorders co-occurring with a primary disease. In children with excess body weight, comorbid conditions can be metabolic, cardiovascular, respiratory, gastrointestinal, musculoskeletal, endocrine, and psychological in nature. Early identification and management of these conditions are essential to prevent long-term complications and improve quality of life. This article reviews the most common comorbid conditions associated with excess body weight in children and discusses their clinical significance.